Prospects of Using Hydrogen Microaddition to Improve Diesel Engine Ecological Indicators - Avramenko, A.M.; Lievtierov, A.M.; Bhantsev, V.M.; Hladkova, N.Yu.; Kirieieva, V.M. (Проблеми машинобудування, 2019)
The generation and use of hydrogen, on board a vehicle, as a microaddition to normal engine fuel is justified as follows. First, the activation of combustion processes in the engine cylinder and, accordingly, fuel combustion completeness increase, which helps reduce the level of mass emissions of SPs and unburned hydrocarbons with the exhaust gases from ICEs. Secondly, such an approach makes it possible to reduce the level of load on the regular exhaust gas neutralization systems of modern vehicle engines, and increase the reliability of their work and their resource. The design of the on-board small-size electrolyzer and its control algorithm are developed. Compre-hensive motor studies of the influence of hydrogen microadditions to diesel fuel on the effective 1H 8.5 / 11 diesel engine performance and the toxicity of its exhaust gases were carried out. Генерування на борту автомобіля та використання водню як мікродомішки до штатного палива двигуна обґрунтовується таким. Підвищується активація процесів згоряння у циліндрі двигуна та, відповідно, збільшується повнота згоряння палива, що сприяє зниженню рівня масових викидів твердих частинок та незгорілих вуглеводнів з відпрацьованими газами ДВЗ. Крім того, такий підхід дозволяє знизити рівень навантаження на штатні системи нейтралізації відпрацьованих газів ДВЗ сучасних транспортних засобів, підвищити надійність їхньої роботи та збільшити ресурс. Розроблено конструкцію бортового малогабаритного електролізера та алгоритм його керування. Проведено комплексні моторні дослідження впливу мікродомішок водню до дизпалива на ефективні показники дизеля 1Ч 8,5/11 та токсичність його відпрацьованих газів. Генерирование и использование на борту автомобиля водорода в качестве микропримеси к штатному топливу двигателя обосновано следующим. Во-первых, увеличивается активация процессов сгорания в цилиндре двигателя и, соответственно, полнота сгорания топлива, что способствует снижению уровня массовых выбросов твердых частиц и несгоревших углеводородов с отработавшими газами ДВС. Во-вторых, такой подход позволяет снизить уровень нагрузки на штатные системы нейтрализации отработавших газов двигателей современных транспортных средств, повысить надежность их работы и увеличить ресурс. Разработана конструкция бортового малогабаритного электролизера и алгоритм его управления. Проведены комплексные моторные исследования влияния микропримесей водорода к дизельному топливу на эффективные показатели дизеля 1Ч 8,5/11 и токсичность его отработавших газов.